PERTUMBUHAN ENTRES BERBAGAI KLON KAKAO (Theobroma cacao L.) PADA UMUR BATANG BAWAH BERBEDA - Akbar, Alfian; Kadekoh, Indrianto; Adelina, Enny (AGROTEKBIS, 2017)
Cacao is the most plantion crop that be developed and cultivated by farmer at Central Sulawesi Province. The objective of this research was to find out the age of rootstock for the growth of entries in clone of cacao Sulawesi 1, Sulawesi 2, and clone 45. The research began on February until April 2016 at Labuan Toposo Village, Labuan district, Donggala regency, Central Sulawesi. The research used two factors random design. The first factors is the using of different clone consist of Sulawesi 1, Sulawesi 2, and clone 45. The second is the using of local rootstock consist of age 1 month, 2 months, 3 months and 4 months. The data analysis was ANOVA analysis if treatment shown significance then continue to use BNJ test at 5%. The research result showed no difference the age of rootstock toward thr growth of entries in each clone. But the 4 months rootstock growth better. There was no difference of clone toward the growth of entries to each rootstock. but clone 45 growth better. Keywords: Cocoa, clone, entries growth, grafting, rootstock age.